14x - 14 = 2x + 46 14x - 2x = 46 + 14 12x = 60 x = 5
2x + 12x = 14x then include the -9 so the asnwer is 14x-9.
4x2 + 28x + 49 = 4x2 + 14x + 14x + 49 = 2x(2x + 7) + 7(2x + 7) = (2x + 7)(2x + 7) or (2x + 7)2
x=7
2x2 + 21x + 49= 2x2 + 14x + 7x + 49= 2x(x + 7) + 7(x + 7)= (x + 7)(2x + 7)
(2x+3)(2x+4)
(4x + 1)(2x + 3)
14x - 14 = 2x + 46 14x - 2x = 46 + 14 12x = 60 x = 5
14x(x + 2)
2x + 12x = 14x then include the -9 so the asnwer is 14x-9.
4x2 + 28x + 49 = 4x2 + 14x + 14x + 49 = 2x(2x + 7) + 7(2x + 7) = (2x + 7)(2x + 7) or (2x + 7)2
3x/7 + 5y/14x = 3x*2x/(7*2x) + 5y/14x = (6x2 + 5y)/14x
If that's +14x + 3, the answer is (2x + 3)(4x + 1)
5x+8x+3x-2x = 14x
x=7
2x2 + 21x + 49= 2x2 + 14x + 7x + 49= 2x(x + 7) + 7(x + 7)= (x + 7)(2x + 7)
yes, and it is 14x